2019
DOI: 10.5455/medarh.2019.73.149-153
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection in Pregnancy - Our Experiences

Abstract: Introduction: Cytomegalovirus (CMV) infection is ubiquitous. It affects all age groups, and its clinical picture ranges from mild to severe, especially as a congenital infection in neonates. Aim: To determine frequency of CMV infection in pregnant women in Tuzla Canton (TC) and the risk factors that lead to the infection. Methods: This prospective study included 300 pregnant women from TC aged 18 to 42 years. CMV serology was performed on all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…The European studies showed widely differing levels of immunity to CMV in childbearingaged women. Compared to the seroprevalence of 70.5% observed in our study, very high CMV seropositivity was found in Bosnia and Herzegovina (93%) [54], moderate seropositivity in Italy (70.8%) [55] and Western Europe (73.2%) [56], and lower seroprevalence in the United Kingdom (49%) [57], France (45.6%) [58], Germany (42.3-45.2%) [59,60], and Norway (62.8%) [42]. Studies from Poland showed CMV seroprevalence rates of 76.7% [61] and 62.4%, respectively [62].…”
Section: Discussioncontrasting
confidence: 87%
“…The European studies showed widely differing levels of immunity to CMV in childbearingaged women. Compared to the seroprevalence of 70.5% observed in our study, very high CMV seropositivity was found in Bosnia and Herzegovina (93%) [54], moderate seropositivity in Italy (70.8%) [55] and Western Europe (73.2%) [56], and lower seroprevalence in the United Kingdom (49%) [57], France (45.6%) [58], Germany (42.3-45.2%) [59,60], and Norway (62.8%) [42]. Studies from Poland showed CMV seroprevalence rates of 76.7% [61] and 62.4%, respectively [62].…”
Section: Discussioncontrasting
confidence: 87%
“…For the treatment for virus, the administration of high-avidity immunoglobulin (HIG) to prevent maternal-fetal CMV transmission is a must in the first trimester pregnancy (124). After transmission, administration of HIG can also be considered to either prevent a symptomatic infection at birth or lessen the symptoms (125). The result from Ville et al indicates that high-dosage valacyclovir given is effective for improving the outcome of moderately symptomatic infected fetuses for virus infection (126).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Obviously, he rejects the definition of Islam as individual faith: he proposes a collective and public morality rather than the individual and inner ethic put forward by Fikret Karčić. But he also criticises the definition of Islam as common culture, and denounces this part of the Muslim intelligentsia "that is conscious of the role of Islam in the national awakening of its people, but gives it first of all a cultural and traditional meaning, and very little real significance in [everyday] life" 79 . In his eyes, "those who believe that it is possible to be linked with Islam in an irregular and superficial way, to apply some of its precepts and to neglect others, should be aware of their inconsistency, and even of a certain hypocrisy.…”
Section: Fikret Karčić: Islam As Individual Faithmentioning
confidence: 99%